PARADOKS PURBAYA EFFECT: FENOMENA BOTTLENECK PEMBIAYAAN SEKTOR UMKM DI TENGAH LIKUIDITAS JUMBO DAN PERSPEKTIF EKONOMI ISLAM - Setyadi, Wendi Hadi; Irham Asfy Putra; Dwi Surya Atmaja; Luqman Luqman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The liquidity injection policy utilizing the Accumulated Budget Surplus (SAL) of IDR 200 trillion aims to create the